Numerical analysis of fishtailing motion, buoy kissing and pullback force in a catenary anchor leg mooring (CALM) moored tanker system - Ju X.; Amaechi C.V.; Dong B.; Meng X.; Li J. (Elsevier Ltd, 2024)
The catenary anchor leg mooring (CALM) sys tem is one of the most complex hydrodynamic systems in terms of hydrodynamic theory. This complexity comes from a large amount of interaction between the buoy, its mooring legs, hawsers, and the moored tanker. A dynamic simulation analysis of a CALM moored tanker system is carried out in this research. A double spring hydrodynamic response system model composed of Anchoring-Buoy and Hawser-Tanker established for the CALM system in the given environmental conditions with the method of time domain coupling simulation, correlation, and comprehensive analysis simulations of the fishtailing motion, buoy kissing, hawser capacity, and pullback force. A numerical analysis shows that without pullback force, fishtailing occurs often. A pullback force of 800 kN in line with the tanker's centerline effectively reduces the yaw motion and preserves a safe distance between the tanker and the buoy, so fishtailing occurs less often, and buoy kissing does not occur. Thus, the pullback force of 800 kN represents astern propulsion and a pullback tug, as it significantly improves the behavior of the moored tanker in relation to the buoy. Therefore, it is recommended that a tug is always present while a tanker is moored to the CALM system. 2023